Institutional differences and local government performance : evidence from property tax assessment quality - Kim, Soojin (2020)
This article examines the relationship between institutional differences embedded in local governance structures and government performance in the specific context of property assessment. In order to provide deeper insight into why certain governance structures perform better than others, we focus on the impact of nested levels of institutions—constitutional-level and substantive-level rules of governance—beyond the conventional perspective of the form of government. Based on panel data of cities and towns in New York State between 1993 and 2010, our analysis indicates that, among other institutional arrangements, municipalities employing the council–manager form with appointed assessors are most likely to achieve higher levels of assessment quality (uniformity) of the residential property. This indicates that having politically independent (more career-oriented), low-powered appointed governance structures rather than politically risk-averse (more voter-oriented), high-powered elected counterparts are more likely to be effective at reducing risk in tax equity issues, thus providing better financial performance.